Vectors of research practice in the field of «konisskovedenie» at the present stage - Somov, Sergey E. (Journal of the Belarusian State University. Philology, 2025)
The main directions of modern research practice concerning the life, activities and creativity in the East Slavic, primarily Belarusian, lands of Georgy Konissky, Archbishop of Mogilev and Belarus, one of the outstanding figures of the Enlightenment era, are analysed. It is noted that the interest of modern secular and ecclesiastical scientists is largely focused on the historical role of Saint Georgy in defending the rights of Orthodox Christians of the Polish-Lithuanian Commonwealth to freedom of worship in the second half of the 18th century, as well as in the possibility of the return of Belarusian Uniates to Orthodoxy. It is pointed out that, from a philological perspective, the textual heritage of Georgy Konissky remains little studied due to the inaccessibility of texts, which are bibliographical rarities. Some researchers examine the linguistic composition of the Archbishop’s works, which include, alongside common Russian vocabulary, elements of Ukrainian, Belarusian and Polish languages.